An ERP study on initial second language vocabulary learning. (20th February 2014) - Yum, Yen Na; Midgley, Katherine J.; Holcomb, Phillip J.; Grainger, Jonathan
Abstract This study examined the very initial phases of orthographic and semantic acquisition in monolingual native English speakers learning Chinese words under controlled laboratory conditions. Participants engaged in 10 sessions of vocabulary learning, four of which were used to obtain ERPs. Performance in behavioral tests improved over sessions, and these data were used to define fast and slow learners. Most important is that ERPs in the two groups of learners revealed qualitatively distinct learning patterns. Only fast learners showed a left‐lateralized increase in N170 amplitude with training. Furthermore, only fast learners showed an increased N400 amplitude with training, with a distinct anterior distribution. Slow learners, on the other hand, showed a posterior positive effect, with increasingly positive‐going waveforms in occipital sites as training progressed. Possible mechanisms underlying these qualitative differences are discussed.